2008
DOI: 10.1002/j.2161-4296.2008.tb00414.x
|View full text |Cite
|
Sign up to set email alerts
|

Deeply Integrated GPS/Low-Cost IMU for Low CNR Signal Processing: Concept Description and In-Flight Demonstration

Abstract: A deeply integrated GPS/low-cost IMU system is developed and applied to re-acquire and track GPS signals with low carrier-to-noise ratio (CNR). The system provides continuous carrier phase tracking without requiring the knowledge of navigation data bits. Flight data with a 90-degree turn are applied to demonstrate re-acquisition and continuous carrier phase tracking of 15 dB-Hz GPS signals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 5 publications
(16 reference statements)
0
33
0
Order By: Relevance
“…If the coherent integration time extends beyond the data bit boundary, then the data bits need to be accounted for in some way. A number of approaches have been suggested in the literature for dealing with these unknown modulations (see, for example, Soloviev et al (2008) and references therein), they are not considered further herein.…”
Section: Effect On Measurementsmentioning
confidence: 99%
“…If the coherent integration time extends beyond the data bit boundary, then the data bits need to be accounted for in some way. A number of approaches have been suggested in the literature for dealing with these unknown modulations (see, for example, Soloviev et al (2008) and references therein), they are not considered further herein.…”
Section: Effect On Measurementsmentioning
confidence: 99%
“…Though the Doppler aiding showed smaller carrier phase errors than delta-Doppler aiding, the difference is not much. Several articles developed complicated aiding algorithms and demonstrated superior performances [5], [8]. On the other hand, this paper has shown that even a very simple method (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…If cycle slips occur in several channels, the corresponding smoothing procedures have to be restarted, and would cause a missed approach. An implementation of an inertial sensor will improve the tracking performance if the Doppler frequency caused by aircraft dynamics is compensated by the inertial measurements [3]- [5]. In the present paper we describe a prototype INS-aided GPS receiver for the aircraft navigation complex, that is under development by JAXA, intended in particular to be engaged in approach and landing.…”
Section: Introductionmentioning
confidence: 99%
“…The processing gain associated with the non-coherent integration has been documented in [15]. There are several methods that allow block-based software acquisition algorithms to overcome the impact of the navigation data bit on acquisition [1], [12]. Therefore, we omit the weak signal navigation data issue here to focus on the performance of interference cancellation.…”
Section: Interference Cancellation Algorithm Performance Evaluationmentioning
confidence: 99%